What about the children! : masculinities, sexualities and hegemony - Riggs, Damien W. (Cambridge Scholars, 2010)
What About the Children! takes up the important task of examining the role of hegemonic masculinities in propping up a normative social order in which children are constructed as the property of adults. By examining adult-child relations in the context of.